Fetal transient tricuspid valve regurgitation: sonographic features and clinical evolution. (3rd August 2021) - Clerici, Graziano; Romanelli, Maila; Tosto, Valentina; Tsibizova, Valentina; Di Renzo, Gian Carlo
Abstract: Purpose: To analyze the prevalence, the sonographic features, the clinical evolution and significance of fetal tricuspid valve regurgitation (TR). Study design: This is a prospective study. Serial ultrasound examinations were performed at 20–23, at 26–29 and at 30–34 gestational weeks in 675 consecutive singleton pregnancies with fetal normal growth and normal cardiac anatomy. The fetal tricuspid valve regurgitation was classified according to its duration, to the peak of jet maximum velocity and to its maximum spatial extension. A clinical examination and echocardiography were performed in neonates after birth. Results: During the first examination (20–23 weeks), 32 cases of tricuspid valve regurgitation were identified. The prevalence of tricuspid regurgitation was 4.74%. The large majority of TR cases were not-holosystolic (87.5%), with a maximum velocity below 2 m/sec (80–130 cm/sec in 84% cases and 180–200 cm/sec in 16% cases) and with a little spatial extension (type I or II in 87.5% cases). Following this hemodynamic phenomenon during the following weeks, we found that it disappeared around 29 weeks in all cases. Conclusions: Tricuspid regurgitation observed during the second trimester can be considered a transient and functional hemodynamic phenomenon, without apparent pathological significance.